3D Printing of Lotus Root‐Like Biomimetic Materials for Cell Delivery and Tissue Regeneration. Issue 12 (26th October 2017) - Feng, Chun; Zhang, Wenjie; Deng, Cuijun; Li, Guanglong; Chang, Jiang; Zhang, Zhiyuan; Jiang, Xinquan; Wu, Chengtie
Abstract: Biomimetic materials have drawn more and more attention in recent years. Regeneration of large bone defects is still a major clinical challenge. In addition, vascularization plays an important role in the process of large bone regeneration and microchannel structure can induce endothelial cells to form rudimentary vasculature. In recent years, 3D printing scaffolds are major materials for large bone defect repair. However, these traditional 3D scaffolds have low porosity and nonchannel structure, which impede angiogenesis and osteogenesis. In this study, inspired by the microstructure of natural plant lotus root, biomimetic materials with lotus root‐like structures are successfully prepared via a modified 3D printing strategy. Compared with traditional 3D materials, these biomimetic materials can significantly improve in vitro cell attachment and proliferation as well as promote in vivo osteogenesis, indicating potential application for cell delivery and bone regeneration. Abstract : Inspired by the microstructure of lotus root, lotus root‐like biomimetic materials are successfully prepared via a modified 3D printing strategy with different kinds of materials, channel numbers, shapes, porosity, surface area, and mechanical properties. The biomimetic materials significantly improve in vitro cell attachment and proliferation as well as in vivo osteogenesis, indicating potential application for cell delivery and bone regeneration.